An Analysis Of The Role Of The Mitra Dhuafa Cooperative (Komida) In Awakening The Economic Potential Of Women In The Pase Raya Sub-District, Aceh Jaya District - Najla, Najla (Jurnal Pengabdian Bakti Akademisi, 2025)
Mitra Dhuafa Cooperative (KOMIDA) society, especially for economically weak women, as a financial institution that focuses on providing business capital assistance for the small and medium economic business sector has been supportive in sustaining the lives of micro-enterprises, home-based businesses, and low-income women in general. This thesis research aims to find out the role of Koperasi Mitra Dhuafa (KOMIDA) in raising the economic potential of women in Pasie Raya District, Aceh Jaya Regency. This research is a qualitative descriptive research. The data used is primary data obtained from direct interviews with the management of the Mitra Dhuafa Cooperative Branch and members in Pulo Tinggi, Lhok Guci, and Tuwi Perya Villages in Pasie Raya District, Aceh Jaya Regency. Data collection techniques using interview techniques, observation, and documentation. Data analysis techniques in this study are 1) data reduction, 2) data presentation, 3) data analysis, and conclusion drawing. The results showed that: (1) the implementation of savings and loan business unit activities, creating business entrepreneurs for women who allow community potential to develop (2) the existence of Mitra Dhuafa Cooperative, can make it easier for women to generate existing potential through capital loans so that they can improve the economy better.